Parent-adolescent communication on adolescent sexual and reproductive health in sub-Saharan Africa: a qualitative review and thematic synthesis - Ijeoma Usonwu; Raheelah Ahmad; Katherine Curtis-Tyler (BMC, 2021)
Key messages Adolescents in sub-Saharan Africa remain at high risk for sexually transmitted infections, female genital mutilation, and early pregnancy. Adolescents mostly view sex-related discussions with parents as uncomfortable, and interactions are driven by fear of personal, social, and economic consequences of sexual risk-taking behaviour. Parents recognise their lack of capacity to engage with adolescents and are influenced by cultural norms and religious beliefs. Future research needs to address the current imbalance of adult versus adolescent voices in published work and also ensure a creation of space for conversations about sexuality with sexual and gender minority youth in the Lesbian, Gay, Bi-sexual, Transgender, Queer, Intersex, and Asexual communities.